Communication Exclusivity in Disseminating Local Sufism to Wetu Telu Islamic Community in Kayangan Village, Kayangan District, North Lombok - Karliade Aji Saputra (Jurnal Ar Ro'is Mandalika (Armada), 2021)
Exclusive communication is one of the techniques or methods used by the Sasak community (Lombok tribe, NTB) in maintaining the values and norms contained in each of its teachings known as Islam Wetu Telu, which in the scientific tradition of Sufism is known as local Sufism, namely Sufism which has adapted to local wisdom. The objectives of this study are: a) to determine the causes of communication exclusivity in the spread of local Sufism in the Wetu Telu Islamic community in Rebakong Hamlet, Kayangan Village; b) to find out how the process of exclusivity of communication in the dissemination of local Sufism teachings of Islam Wetu Telu in Rebakong Hamlet, Kayangan Village; c) to find out the supporting and inhibiting factors in the exclusivity of communication that occurs in the environment of Wetu Telu Muslims who spread local Sufism teachings. While in data collection using documentation, interviews and observations. And testing the credibility of its data using triangulation. The results of this study are: a) the causes of exclusivity of communication in the Wetu Telu Islamic community include: (1) confidentiality of local Sufism content that should not be disseminated publicly, (2) maintaining existing local wisdom, (3) maintaining previously believed values. b) The process of spreading local Sufism is only carried out to the Jama'ah. The study carried out is not bound by schedule and usually before conducting the study, the character begins with small talk so that pilgrims who study local Sufism teachings have no difficulty and quickly understand the teachings. c) Factors supporting the exclusivity of communication in the dissemination of local Sufism teachings include high motivation of local Sufism disseminators to continue to spread these teachings. In addition, there is encouragement and enthusiasm given by pilgrims, the surrounding community, and even government agencies. There are inhibiting factors such as false accusations of local Sufism and conflicts that lead to social exclusion.